Optimal Placement of Distribution Generating in Distribution System Based on Cost worth & System Reliability indices. - Saeed, Dr. Wafaa (University of Thi-Qar Journal, 2019)
Electrical power systems include three functional areas: generation, transmission and distribution systems. Evaluate the reliability of the whole system is very complex so the present research is limited on evaluate the reliability of radial distribution system. Since the demand loads have continuously growth and uncertainties it became one of the important things to be observed, so that we can forecast an accurate demand loads in the future .To ensure the continuity of providing demand loads and the possibility of covering the expected increase demand the technology of injected Distributed Generation in a radial distribution system through circuit breaker was adoption. DG works to generate energy to cover the increased in demand loads or to compensate the shortfall in generation during a Failure. To enhances the reliability of the test system optimal location and size of DG should be identifies. Basic reliability indices for load points and the overall system have been developed. A additional reliability (i.e. cost worth& System Reliability) indices are suggested. The cost worth indices serve as a guide to locate position where reliability needs to be supported. The suggested approach has been tested on Roy Billinton Test System 6 bus with four radial feeders. The Results that we got from this approach clearly shows the best location and sizing of DG and so support the reliability of the system